2005
DOI: 10.1111/j.0737-1209.2005.22102.x
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Infant Mortality Rates Using the Perinatal Periods of Risk Model

Abstract: Despite decreases in the last 50 years, infant mortality rates in the United States remain higher than in other industrialized countries. Using overall infant mortality rates to determine the effectiveness of interventions does not help communities focus on particular underlying factors contributing to static, and sometimes increasing, community rates. This study was designed to determine and rank contributing factors to fetal-infant mortality in a specific community using the Perinatal Periods of Risk (PPOR) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 9 publications
0
11
0
1
Order By: Relevance
“…To understand the limitations of prenatal care and programs linked to it, a review of the Perinatal Periods of Risk (PPOR)-an analytic strategy developed by the Atlanta-based World Health Organization Collaborating Center for Reproductive Health and applied nationally by CityMATCH-demonstrates the need to consider broader systems of care for different population groups (12). PPOR raises questions about the ability of prenatal care to intervene on risks for extremely early delivery given the short window of opportunity.…”
Section: Wwwannualreviewsorg • Infant Mortality Disparities and Carementioning
confidence: 99%
“…To understand the limitations of prenatal care and programs linked to it, a review of the Perinatal Periods of Risk (PPOR)-an analytic strategy developed by the Atlanta-based World Health Organization Collaborating Center for Reproductive Health and applied nationally by CityMATCH-demonstrates the need to consider broader systems of care for different population groups (12). PPOR raises questions about the ability of prenatal care to intervene on risks for extremely early delivery given the short window of opportunity.…”
Section: Wwwannualreviewsorg • Infant Mortality Disparities and Carementioning
confidence: 99%
“…Previous PPOR analyses have found that the maternal health/prematurity category, which by definition consists of all VLBW births and fetal deaths, is often the greatest contributor to excess infant mortality [6–12]. A PPOR analysis in Kansas City found that deaths due VLBW were a significant issue among African Americans [7].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have recently been published on the importance of improving preconception care in order to improve birth outcomes (Atrash et al., ). Other researchers utilizing the PPOR approach have recommended preconception care as an intervention to reduce infant mortality rates (Besculides & Laraque, ; Burns, ; Cai, Hoff, Dew, Guillory, & Manning, ).…”
mentioning
confidence: 99%